ANALISIS KINERJA KEUANGAN DAERAH PADA DINAS BINA MARGA PROVINSI SULAWESI SELATAN - A. Husnawaty AR A. Husnawaty AR (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2013)
The purpose of this research is to know the government's financial performance against regional expenditure At the Highways Agency South Sulawesi in the last four years (2009-2012) and to reveal the effectiveness and efficiency of the government 's financial performance against regional expenditure achieved by the local government at the Office South Sulawesi Provincial Highways in the last four years (2009-2012). The method of analysis used in this research is descriptive method (descriptif quantitative analysis method), ie by setting concept in the calculation of financial ratios measuring the financial performance, by calculating the ratio of the actual financial budget set out in the budget and budget realization report. From the results of the analysis and discussion in this study are : First ; assessment of financial performance over the last 4 years local look -effectiveness ratio of receipts levy on Highways Agency shows that the average increase of 84.39 % per year with a fairly effective category , in 2010 a decline in the effectiveness of 82.17 % which is less effective due in 2010 to levy on legalization eliminated, and in 2012 saw an increase of 113.88 % with very effective due to the increase in the categories of activities that are managed by the Highways Agency to use RPJK increased . Second, for the efficiency of personnel expenditure in 2009 to 2012 to categorize quite effective because the activity remained without, for the efficiency of spending on goods/services in the year 2009 to the year 2012 is also considered quite effective due to the use of spending on goods/services remain without any change , while the efficiency of capital expenditure in 2009 amounted to 95.33 % , in 2011 was 95.55 % in 2012 and increased by 98.44 % categorized quite effective , whereas in 2010, a decrease of 68.68 % .